Monitoring of berillium content in waste water of nsc kipt before and after purification - Gordienko, Yu.A.; Mazilov, A.A.; Nikulina, V.Ya.; Sosipatrov, M.V.; Tkachenko, V.N. (Вопросы атомной науки и техники, 2020)
In this paper, the results of applied studies on beryllium content in waste water of NSC KIPT before and after purification are presented. The most optimal conditions of physicochemical processes used in the water treatment are defined. The results obtained allow one to make a conclusion that the content of beryllium in waste water under investigation before and after purification does not exceed the threshold limit value (TLV) and is under control. All chemical analyzes were carried out by the metrologically certified laboratory of “Radiation Research and Environmental Protection” NSC KIPT. Відображено результати прикладних досліджень вмісту берилію в стічних водах ННЦ ХФТІ до і після очищення. Визначено найбільш оптимальні умови проведення фізико-хімічних процесів очищення води. Отримані результати дозволяють зробити висновок, що вміст у досліджуваних стічних водах берилію після очищення не перевищує гранично допустимих концентрацій і знаходиться під контролем. Усі хімічні аналізи проведено метрологічно атестованою лабораторією «Радіаційні дослідження і охорона навколишнього середовища» ННЦ ХФТІ. Oтражены результаты прикладных исследований содержания бериллия в сточных водах ННЦ ХФТИ до и после очистки. Определены наиболее оптимальные условия проведения физико-химических процессов очистки воды. Полученные результаты позволяют сделать вывод, что содержание в исследуемых сточных водах бериллия после очистки не превышает предельно допустимых концентраций и находится под контролем. Все химические анализы проведены метрологически аттестованной лабораторией «Радиационные исследования и охрана окружающей среды» ННЦ ХФТИ.